Preferences and beliefs in ingroup favoritism - Everett, Jim A. C.; Faber, Nadira S.; Crockett, Molly (Frontiers in Behavioral Neuroscience, 2015)
Ingroup favouritism – the tendency to favour members of one’s own group over those in other groups – is well documented, but the mechanisms driving this behavior are not well understood. In particular, it is unclear to what extent ingroup favouritism is driven by preferences concerning the welfare of ingroup over outgroup members, versus beliefs about the behaviour of ingroup and outgroup members. In this review we analyse research on ingroup favouritism in economic games, identifying key gaps in the literature and providing suggestions on how future work can incorporate these insights to shed further light on when, why, and how ingroup favouritism occurs. In doing so, we demonstrate how social psychological theory and research can be integrated with findings from behavioral economics, providing new theoretical and methodological directions for future research.